2015
DOI: 10.1093/molehr/gav063
|View full text |Cite
|
Sign up to set email alerts
|

Placental programmed cell death: insights into the role of aquaporins

Abstract: This study was supported by UBACyT 20020090200025 and 20020110200207 grants and PIP-CONICET 11220110100561 grant, and the authors have no conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Located across the cell membrane, AQP3, besides transporting water, glycerol, etc., can also synthesize TG via glycerol kinase catalysis [21]. A previous study showed that inhibiting the expression of AQP3 protein mitigated apoptosis reactions of placenta [7]. Alejandra et al [22] found that silencing of placental AQP3 protein induced early-onset preeclampsia, which was probably attributed to the impaired migration of extravillous trophoblast cells and the failure in the remodeling of maternal spiral arteries afterward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Located across the cell membrane, AQP3, besides transporting water, glycerol, etc., can also synthesize TG via glycerol kinase catalysis [21]. A previous study showed that inhibiting the expression of AQP3 protein mitigated apoptosis reactions of placenta [7]. Alejandra et al [22] found that silencing of placental AQP3 protein induced early-onset preeclampsia, which was probably attributed to the impaired migration of extravillous trophoblast cells and the failure in the remodeling of maternal spiral arteries afterward.…”
Section: Discussionmentioning
confidence: 99%
“…The fluctuation of AQP3 protein has been reported to be closely related to physiological and pathological reactions, such as reproduction, breast secretion, gestational diabetes mellitus, gynecological tumors, hypertensions, and so on [5, 6]. Furthermore, an in vitro study has shown that AQP3 participated in the oxidative stress response and the apoptosis of placenta nourishing cells [7]. Therefore, we speculate that the imbalance of placental AQP3 might be a key cause of preeclampsia as well as a variety of clinical manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that upregulation of AQP3 expression contributes to the proliferative activity of GC cells 3. AQP3 expression has also been implicated in the regulation of cell apoptosis 35,36. But the association between AQP3 expression and cell apoptosis in GC has not been elucidated in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Another study proved that AQP3 has a critical role in the regulation of placental apoptosis in pathological placentas (e.g., in preeclampsia). The loss of water via AQP3 from the cells during the apoptotic volume decrease is important to the progression of apoptosis [ 42 ].…”
Section: Maternal–fetal Fluid Flowmentioning
confidence: 99%